2004
DOI: 10.1300/j083v43n01_04
|View full text |Cite
|
Sign up to set email alerts
|

Senior Citizens Centers

Abstract: This study extends exploration of what senior centers offer, who participates, and what they gain. Center staff surveyed 856 participants in 27 senior centers regarding personal characteristics, program participation, and acquisition of vital information. Although senior centers are considered conduits for group activities and enrichment for older citizens, this investigation indicates that personal characteristics of participants exert a notable influence on the experience and perceived benefits of activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 8 publications
2
27
1
Order By: Relevance
“…12 This older adult population consumes a disproportionate amount of prescription and non-prescription drugs, the use of which confers disproportionate risk. 13 Across the US, persons 65 years of age and older are twice as likely to require an emergency department visit due to an adverse drug event compared with younger adults.…”
Section: Educational Activity and Settingmentioning
confidence: 99%
“…12 This older adult population consumes a disproportionate amount of prescription and non-prescription drugs, the use of which confers disproportionate risk. 13 Across the US, persons 65 years of age and older are twice as likely to require an emergency department visit due to an adverse drug event compared with younger adults.…”
Section: Educational Activity and Settingmentioning
confidence: 99%
“…Extensive research has shown the influence that senior centers have on older adult populations (Aday et al, 2006;Chen et al, 2008;Fulbright, 2010;Turner, 2004). Fulbright (2010) found that a large number of older adults feel that their lives improved after taking part in activities at a senior center.…”
Section: Senior Centersmentioning
confidence: 99%
“…Chen et al (2008) recommended such programs be implemented in senior centers, especially because the results exhibited significant improvements in the older adult sample. Turner (2004) conducted an extensive exploration into the influence of senior center activity participation. The sample included 856 WINTER 2015 PSI CHI JOURNAL OF PSYCHOLOGICAL RESEARCH Subjective Age, Activity, and Depression | Cerino and Leszczynski older adults from 27 senior centers reporting information regarding their participation in various cognitive and physical activities offered at their centers.…”
Section: Senior Center Activitiesmentioning
confidence: 99%
See 2 more Smart Citations